Ocular Pharmacokinetics, Safety and Efficacy of Intracameral Moxifloxacin 0.5% Solution in a Rabbit Model*. (April 2013) - Asena, Leyla; Akova, Yonca A.; Goktaş, Mustafa T.; Bozkurt, Atilla; Yaşar, Ümit; Karabay, Gülten; Demiralay, Ebru
Abstract Purpose: This study was carried out to determine the ocular pharmacokinetics, efficacy and potential endothelial toxicity of moxifloxacin (MF) after a single intracameral bolus injection of 500 µg/0.1 ml in a rabbit model. Materials and methods: Forty-eight eyes of 24 New Zealand White Rabbits were separated into six groups, each including four rabbits. 0.1 ml of 0.5% intracameral moxifloxacin (500 µg) injection was injected to the right eyes and 0.1 ml of balanced salt solution to the left eyes (control). Aqueous humor (AH) and vitreous samples were collected at the 0.5th, 1st, 3rd, 6th, 12th and 24th hours from both eyes of group 1, 2, 3, 4, 5 and 6, respectively. MF concentrations were determined by high performance liquid chromatography. These were compared with the minimum inhibitory concentrations (MIC) and mutant prevention concentrations (MPC) for frequent endophthalmitis pathogens. Electron and light microscopical evaluation of the corneas were performed. Results: Moxifloxacin reaches higher concentration than the MIC of all common endophthalmitis pathogens in the AH and exceeds the mutant prevention concentration levels for Streptococcus pneumonia, Streptococcus viridans, flouroquinolone susceptible Coagulase-negative staphylococcus and flouroquinolone susceptible Staphylococcus aureus for 6 h. The half-life of moxifloxacin in the AH was 2.2 h. Electron and light microscopic evaluation revealed no noticeable sign of toxicity. Conclusions: Peroperative intracameral moxifloxacin injection for endophthalmitis prophylaxis is a safe and effective method in uncomplicated phacoemulsification surgery.